KOMPENSASI, KEPUASAN KERJA DAN WORK–LIFE BALANCE TERHADAP LOYALITAS KARYAWAN - Uhta Ferdian Pratama Sulistyo; Syarif Ali (Fakultas Ekonomi Dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2023)
This study aims to determine the effect of Compensation, Job Satisfaction, Work-life Balance onEmployee Loyalty at PT Panorama JTB Tours Indonesia. The selected population is all employees of PT Panorama JTB Tours using a saturated sample of 50 employees. The use of analytical tools in this study is Partial Least Square (PLS). The results obtained in this study are (1) Compensation has a positive and significant effect on employee loyalty. (2) Job satisfaction has a positive and significant effect on employee loyalty. (3) Work – life balance has a positive and significant effect on employee loyalty. (4) There is a simultaneous influence on employee loyalty of PT Panorama JTB Tours Indonesia. Keywords: Employee loyalty; Compensation; Job Satisfaction and Work – life Balance.